2022
DOI: 10.3389/fpsyg.2022.895930
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Patterns of University Students Study Crafting and the Relationships to Exhaustion, Well-Being, and Engagement

Abstract: Job crafting has been established as a bottom-up work design instrument for promoting health and well-being in the workplace. In recent years, the concepts of job crafting have been applied to the university student context, proving to be positively related to student well-being. Building on person-centered analyses from the employment context, we assessed approach study crafting strategy combinations and the relationships to students’ exhaustion, study engagement, and general well-being. Data from 2,882 Germa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 72 publications
0
4
0
2
Order By: Relevance
“…Meta‐analytic evidence indicates that job crafting interventions can significantly increase job crafting behavior and engagement (Oprea et al, 2019). The concept of job crafting has recently been incorporated into the SD–R framework as study crafting (cf., Choi & Shin, 2018; Dormann & Guthier, 2019; Mülder et al, 2022), but no interventions to increase study crafting behavior exist, despite the possibility that such interventions could positively impact higher education students as well (Körner et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Meta‐analytic evidence indicates that job crafting interventions can significantly increase job crafting behavior and engagement (Oprea et al, 2019). The concept of job crafting has recently been incorporated into the SD–R framework as study crafting (cf., Choi & Shin, 2018; Dormann & Guthier, 2019; Mülder et al, 2022), but no interventions to increase study crafting behavior exist, despite the possibility that such interventions could positively impact higher education students as well (Körner et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…First, universities might include courses in their curriculum that focus on the use of strategies to cope with university demands by working on potential resources, such as actively searching for social support or time management strategies (Jacobs & Dodd, 2003; Vizoso et al, 2019; Wyatt et al, 2017). For instance, Mülder et al (2022) suggested supporting students in setting goals that are measurable, achievable, realistic, and timely. Second, interventions might aim at shifting students’ appraisal tendencies, since emotional exhaustion is more strongly related to the subjective appraisal of study demands than to the actual workload (Jacobs & Dodd, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, future research could extend our research model by including more than two life domains. For example, research looking at working students could investigate spillover processes between study crafting (Körner et al, 2021; Mülder et al, 2022), job crafting, and home crafting. Finally, building on the spillover–crossover model (Bakker & Demerouti, 2013), future research might investigate whether job crafting behaviours first spill over to the home domain and then cross over to workers' spouses.…”
Section: Discussionmentioning
confidence: 99%